Active Efflux Leads to Heterogeneous Dissipation of Proton Motive Force by Protonophores in Bacteria - Dai Le (American Society for Microbiology, 2021)
ABSTRACT Various toxic compounds disrupt bacterial physiology. While bacteria harbor defense mechanisms to mitigate the toxicity, these mechanisms are often coupled to the physiological state of the cells and become ineffective when the physiology is severely disrupted. Here, we characterized such feedback by exposing Escherichia coli to protonophores. Protonophores dissipate the proton motive force (PMF), a fundamental force that drives physiological functions. We found that E. coli cells responded to protonophores heterogeneously, resulting in bimodal distributions of cell growth, substrate transport, and motility. Furthermore, we showed that this heterogeneous response required active efflux systems. The analysis of underlying interactions indicated the heterogeneous response results from efflux-mediated positive feedback between PMF and protonophores’ action. Our studies have broad implications for bacterial adaptation to stress, including antibiotics. IMPORTANCE An electrochemical proton gradient across the cytoplasmic membrane, alternatively known as proton motive force, energizes vital cellular processes in bacteria, including ATP synthesis, nutrient uptake, and cell division. Therefore, a wide range of organisms produce the agents that collapse the proton motive force, protonophores, to gain a competitive advantage. Studies have shown that protonophores have significant effects on microbial competition, host-pathogen interaction, and antibiotic action and resistance. Furthermore, protonophores are extensively used in various laboratory studies to perturb bacterial physiology. Here, we have characterized cell growth, substrate transport, and motility of Escherichia coli cells exposed to protonophores. Our findings demonstrate heterogeneous effects of protonophores on cell physiology and the underlying mechanism.